2020
DOI: 10.1016/j.actpsy.2020.103022
|View full text |Cite
|
Sign up to set email alerts
|

Automatic imitation does not predict levels of prosocial behaviour in a modified dictator game

Abstract: Automatic imitation refers to the automatic tendency to imitate observed actions. Previous research on automatic imitation has linked it to a wide variety of social cognitive processes and functions, although the evidence is mixed and suggestive. However, no study to date has looked at the downstream behavioural effects of automatic imitation. The current research addresses this gap in the literature by exploring the possible relationship between trait-levels of automatic imitation, as measured by the automati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
6
1
Order By: Relevance
“…In both of our high-powered studies, we found no correlation between automatic imitation and belief in free will, suggesting that the two constructs are likely unrelated. Therefore, in line with current research (e.g., Butler et al, 2015;Galang & Obhi, 2020;Genschow, van Den Bossche, et al, 2017;Müller et al, 2013) our findings suggest that the relationship between automatic imitation and interindividual factors is less universal and generalizable than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In both of our high-powered studies, we found no correlation between automatic imitation and belief in free will, suggesting that the two constructs are likely unrelated. Therefore, in line with current research (e.g., Butler et al, 2015;Galang & Obhi, 2020;Genschow, van Den Bossche, et al, 2017;Müller et al, 2013) our findings suggest that the relationship between automatic imitation and interindividual factors is less universal and generalizable than previously reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Although previous research has shown that certain personality traits such as autism (Bird et al, 2007), narcissism (Hogeveen & Obhi, 2013), as well as empathic traits and the ability to take another person's perspective (Cracco et al, 2015) correlate with automatic imitation, other research was not able to replicate some of these findings (Butler et al, 2015;Cracco, Bardi, et al, 2018;Galang & Obhi, 2020;Genschow, van Den Bossche, et al, 2017;Müller et al, 2013;Newey et al, 2019). In line with these failed replications, we find despite high power no support for the idea that interindividual differences are linked to automatic imitation.…”
Section: Theoretical Implicationscontrasting
confidence: 89%
“…These earlier results converge with recent metaanalytic data to demonstrate the powerful influence that orthogonal spatial-compatibility effects can exert on measures of AI acquired in SRC procedures and their potential to obscure relationships between imitation and other aspects of social cognition (Shaw et al, 2017). This raises questions over the associations reported in studies using rotated hand stimuli between AI and social behaviour, as acknowledged in more recent research (Galang & Obhi, 2020;Gordon et al, 2020).…”
Section: Introductionsupporting
confidence: 82%
“…A growing awareness of the strong confounding effect that simple spatial compatibility exerts on measures of AI in SRC tasks has led several studies to attempt to control for this methodological issue. One approach used increasingly to investigate the neurocognitive mechanisms behind imitative tendencies isolated from any simple spatial-compatibility effects is to rotate a left stimulus hand 90°counter-clockwise from participants' perspective (Cook & Bird, 2012;de Guzman, Bird, Banissy, & Catmur, 2016;Farwaha & Obhi, 2020;Galang & Obhi, 2020;Gordon et al, 2020;Hogeveen & Obhi, 2013;Hogeveen et al, 2014). In this orthogonal setup, the fingers of the horizontal response hand move up and down but those of the vertical stimulus hand move left and right, which is considered a way of controlling for any nonsocial spatial influences.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the conclusion that automatic imitation is not affected by group membership fits to several other recent findings illustrating the resilience of automatic imitation against social modulations. For example, recent research found difficulties in replicating correlations between automatic imitation and different interindividual differences including autism-like traits, narcissism, empathy, and perspective taking (Butler et al, 2015 ; Cracco, Bardi, et al, 2018 ; Galang & Obhi, 2020 ; Genschow et al, 2017 ; Müller et al, 2013 ; Newey et al, 2019 ). Likewise, Khemka et al ( 2020 ) could not replicate the finding that sitting in front of a mirror reduces automatic imitation (Spengler et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%